2011
DOI: 10.4236/fns.2011.24048
|View full text |Cite
|
Sign up to set email alerts
|

Iron and Folate Contents of Tajik Legumes

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…The folic acid pattern has revealed 5‐methyltetrahydrofolate as the predominant folate form in cowpea . This is, however, in contrast with Yarbaeva et al who found tetrahydrofolate as the most abundant B vitamin in Tajik cowpea accessions . Concerning vegetative tissues, the partial characterisation performed so far showed that the total folic acid content in leaves was up to five‐fold higher to those described in seeds (3.3–20.1 × 10 −3 g kg −1 ) …”
Section: Nutritional Composition Of Cowpeamentioning
confidence: 78%
See 1 more Smart Citation
“…The folic acid pattern has revealed 5‐methyltetrahydrofolate as the predominant folate form in cowpea . This is, however, in contrast with Yarbaeva et al who found tetrahydrofolate as the most abundant B vitamin in Tajik cowpea accessions . Concerning vegetative tissues, the partial characterisation performed so far showed that the total folic acid content in leaves was up to five‐fold higher to those described in seeds (3.3–20.1 × 10 −3 g kg −1 ) …”
Section: Nutritional Composition Of Cowpeamentioning
confidence: 78%
“…Of particular importance are the high contents of calcium (383–10 620 and 398.0–8050.0 × 10 −3 g kg −1 in seeds and leaves, respectively), zinc (8.1–118.0 and 3.4–129.1 × 10 −3 g kg −1 in seeds and leaves, respectively), and iron (6.9–218.0 and 16.2–772.9 × 10 −3 g kg −1 in seeds and leaves, respectively) . This mineral composition emphasises the value of cowpea fulfilling the recommended daily intake in a similar way as other legumes . Still, there is a dearth of information on the mineral composition of cowpea pods, an under‐exploited material from legumes in general, and current data shows lower contents compared with seeds and leaves .…”
Section: Nutritional Composition Of Cowpeamentioning
confidence: 86%
“…19,27−29 These assays include a microbiological method using Lactobacillus rhamnosus 28,29 and HPLC-MS methods. 19,29 Liquid chromatography− mass spectrometry (LC-MS) enables the simultaneous identification and quantification of different folates. In the present study 5-methyl-THF and 10-formyl-THF forms were qualitatively identified to determine the presence of different folate forms.…”
Section: ■ Discussionmentioning
confidence: 99%
“…30 Because most of the folate in legumes remains as THF, the estimates of THF are appropriate as a measure of folate concentrations in lentils. 29 Global biofortification efforts for increased levels of micronutrients in lentils have been limited to a few research groups. 14,16 A few studies have been reported in which staple crops have been determined to have a useful level of genetic variability for micronutrients including iron, zinc, pro-vitamin A, and carotenoids.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Food folate levels have been measured using different analytical methods including HPLC and microbial assays. These assays include a microbiological method using Lactobacillus rhamnosus [26] and HPLC-mass spectroscopy methods [28] which include the extraction (conjugase, enzyme treatment, incubation periods) and deconjugation procedure, which might also explain the differences in the folate value in the foods. [29] The use of trienzyme treatment, with the inclusion of α-amylase and protease in the folate analysis, is often used to enhance the release of the folate that is bound or trapped in the food matrix of proteins and oligosaccharides besides the deconjugation with the folate conjugase, thus enhancing the yield of folate from foods.…”
mentioning
confidence: 99%